2013
DOI: 10.7748/ncyp2013.05.25.4.20.e192
|View full text |Cite
|
Sign up to set email alerts
|

Needs and priorities of young people with human immunodeficiency virus

Abstract: Professionals involved in creating future social policy and commissioning services need to respond to young people's priorities and adapt to the patient's developing sexuality and the changing demographics of young people with HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previous research has discussed the negative experiences of people affected with HIV (Gordillo et al, 2009;Marks, 2008;Purssell, Fanner, & Barnes, 2013). In relation to this, Okwun and Siraj (2010) mentioned that the main goal of counselling sessions must be focused on the emotions of clients affected with HIV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has discussed the negative experiences of people affected with HIV (Gordillo et al, 2009;Marks, 2008;Purssell, Fanner, & Barnes, 2013). In relation to this, Okwun and Siraj (2010) mentioned that the main goal of counselling sessions must be focused on the emotions of clients affected with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to this study, the participants reported feelings of relief as a result of having someone willing to listen to them, that is, they experienced emotional support. People with HIV often experience anger, fear, as well as self-denial (Gordillo et al, 2009;Marks, 2005;Purssell, Fanner, & Barnes, 2013;Haslee Shahril, 2007), which may be related to being unable to share their daily struggles and challenges. Being able to share and tell the counsellor their stories generated feelings of relief, for example, Kama stated that counselling helped him deal with his stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation